Do Disaster Literacy and Mitigation Policy Affect Residents Resettling in Tsunami Prone Areas? Study from the City of Banda Aceh, Indonesia - Khairunnisa Khairunnisa; Yusya Abubakar; Didik Sugianto (Universitas Muhammadiyah Surakarta, 2021)
It has been a decade and a half since the tsunami struck Aceh in 2004. Half of the city of Banda Aceh was destroyed. However, this tsunami-prone area has regained population density with households and communities growing despite the efforts of the local government to socialize disaster literacy and mitigation policy. Have these policies affected people in their decision to resettle in this disaster-prone area? This is the issue considered in this study. It aims to examine and analyse the impact of disaster literacy and mitigation policies on residents’ decision to occupy a post-disaster area in Banda Aceh. This study employs a quantitative approach. It utilises random sampling. A set of questionnaires were distributed among 225 samples (households) across 5 sub-districts in the tsunami red-zone area. These questionnaires have been analysed using SPSS, employing a multiple linear regression technique. The outcome indicated that disaster literacy had a significant positive affect (p value=0.000, β=0.410), while the mitigation policies were not statistically significant for residents’ decisions to resettle in disaster-prone areas. As the tsunami area remains vulnerable, a resulting policy recommendation is for the local government to be more active in disseminating its mitigation policies, and in helping residents to develop a fuller understanding of them (including implications of the disaster risk index and the disaster risk map). This would help achieve and put into practice the objectives of the mitigation policies.